Ponding as a low cost method of wastewater control - Wong, Kien Keong (1980)
Ponding is proposed as a viable low-cost treatment method for both industrial and domestic sewerage effluent. Theoretical considerations were reviewed and discussed in relation to the design of ponds. Different types of pond operations were presented. Both empirical and rational design models were presented. Adoption of such models were deemed closest to a way of designing ponds. General design criteria and performances were listed as guidelines for usage. Application of ponding system for palm oil mill effluent, rubber effluent and domestic sewerage locally were discussed. Some first order kinetic coefficients were calculated for rubber effluents. These constants ranged from 0.065 to 0.27 day-1. Kinetic coefficients for palm oil mill effluent for both completely mixed and plug flow systems were also presented. Insufficient data prevented the derivation of kinetic constants for domestic sewerage oxidation ponds. Costs data were derived from existing palm oil mill effluent anaerobic treatment systems for comparison between ponding and other systems.